Utilizing Recycled Rubber and Municipal Waste Incineration Fly Ash in Cement-Stabilized Clayey Soils - Aouf, Gehan; Alhakim, Ghida; Jaber, Lina (Salehan Institute of Higher Education, 2024)
This study explores an innovative approach combining municipal solid waste incinerator fly ash (MSWIFA), cement, and recycled rubber to enhance soil properties. The research fills a research gap by exploring the synergistic effects of these materials, striving to strike a balance between strength and flexibility in soil stabilization. A total of 123 tests, comprising Proctor compaction and unconfined compression tests, were performed on clayey soil samples treated with varying stabilizer proportions: 10%, 20%, and 30% MSWIFA; 10%, 15%, and 20% cement; and 0%, 5%, and 10% rubber by dry weight. The tests revealed that the ideal blend of 5% rubber, 10% MSWIFA, and 20% cement resulted in a notable 294% increase in unconfined compressive strength and a significant enhancement in soil ductility, presenting a stark contrast to traditional cement-stabilized soils recognized for their brittleness and limited flexibility. This approach not only enhances soil characteristics but also promotes environmental sustainability by utilizing waste materials in the stabilization process. Doi: 10.28991/CEJ-2024-010-11-017 Full Text: PDF